Effect of a plant sterol-enriched spread on biomarkers of endothelial dysfunction and low-grade inflammation in hypercholesterolaemic subjects. (6th December 2016) - Ras, R. T.; Fuchs, D.; Koppenol, W. P.; Schalkwijk, C. G.; Otten-Hofman, A.; Garczarek, U.; Greyling, A.; Wagner, F.; Trautwein, E. A.
Abstract: Plant sterols (PS) lower LDL-cholesterol, an established risk factor for CHD. Endothelial dysfunction and low-grade inflammation are two important features in the development of atherosclerosis. Whether PS affect biomarkers of endothelial function and low-grade inflammation is not well studied. The aim of the present study was to investigate the effect of regular intake of PS on biomarkers of endothelial dysfunction and low-grade inflammation. In a double-blind, randomised, placebo-controlled, parallel-group study, which was primarily designed to investigate the effect of PS intake on vascular function (clinicaltrials.gov: NCT01803178), 240 hypercholesterolaemic but otherwise healthy men and women consumed a low-fat spread with added PS (3 g/d) or a placebo spread for 12 weeks. Endothelial dysfunction biomarkers (both vascular and intracellular adhesion molecules 1 and soluble endothelial-selectin) and low-grade inflammation biomarkers (C-reactive protein, serum amyloid A, IL-6, IL-8, TNF-α and soluble intercellular adhesion molecule-1) were measured using a multi-array detection system based on electrochemiluminescence technology. Biomarkers were combined using z -scores. Differences in changes from baseline between the PS and the placebo groups were assessed. The intake of PS did not significantly change the individual biomarkers of endothelial dysfunction and low-grade inflammation. The z -scores for endothelial dysfunction (−0·02; 95 % CI −0·15, 0·11) and low-grade inflammation (−0·04; 95 % CI −0·16, 0·07) were also not significantly changed after PS intake compared with placebo. In conclusion, biomarkers of endothelial dysfunction and low-grade inflammation were not affected by regular intake of 3 g/d PS for 12 weeks in hypercholesterolaemic men and women.